Numerical simulation study of thermal runaway jet fire characteristics of forced air-cooled cylindrical battery module - Xiantong Wu; Yanxin Hu; Tingting Wu; Ziqi Zhuo; Huihe Qiu; Yishun Zhu; Xingyu Li; Run Tang (Case Studies in Thermal Engineering)
To elucidate the spread characteristics of the thermal runaway jet flame in the forced-air-cooled 18650 battery module, a three-dimensional thermal runaway jet fire model is constructed. The process of thermal runaway jet gas passing through the safety valve is modeled as isentropic flow, with the velocity inlet boundary applied to the safety valve of the battery. The combustion of the thermal runaway jet gas is simulated using the Eddy Dissipation model within the volume reaction module. Results indicate that when the second cell (cell 2) undergoes thermal runaway jet combustion, the maximum average temperature in the fluid domain of the air-cooled module rises to 1206.41K. In cells aligned in the same row, those nearer to the downstream end initiate jet fires, resulting in a lower maximum average temperature in the fluid domain. Carbon monoxide generated during thermal runaway is predominantly distributed in the upper section of the air-cooled module, with a maximum concentration of 16787 ppm, posing significant safety risks.